Edukasi Manajemen Hipertensi dan Perilaku Hidup Bersih dan Sehat (PHBS) dalam Upaya Meningkatkan Kemandirian Kesehatan Keluarga - Nurma Zela Gustina; Naila Alya Muhbita; Viola Putria Tiwi (Semar: Jurnal Pengabdian Kepada Masyarakat, 2026)
Chronic health problems such as hypertension are often exacerbated by poor medication adherence and unhealthy lifestyles at the family level. This community service program aims to improve family knowledge and independence in managing hypertension and implementing Clean and Healthy Living Behaviors (PHBS). The method used was family nursing care, which included assessment, health education through leaflets, and self-care demonstrations for two partner families in Kacang Pedang Village. The results of the activity showed an increase in family understanding of the dangers of hypertension complications, the importance of regular check-ups at health facilities (Puskesmas), and the implementation of cough etiquette and environmental cleanliness. The conclusion of this community service program is that health education focused on family support systems is effective in changing perceptions of traditional medicine towards medical treatment and increasing family independence scores.